Mid infra-red hyper-spectral imaging with bright super continuum source and fast acousto-optic tuneable filter for cytological applications. (May 2015) - Farries, Mark; Ward, Jon; Valle, Stefano; Stephens, Gary; Moselund, Peter; van der Zanden, Koen; Napier, Bruce
Abstract: Mid-IR imaging spectroscopy has the potential to offer an effective tool for early cancer diagnosis. Current development of bright super-continuum sources, narrow band acousto-optic tunable filters and fast cameras have made feasible a system that can be used for fast diagnosis of cancer in vivo at point of care. The performance of a proto system that has been developed under the Minerva project is described.